A quality control portal for sequencing data deposited at the European genome–phenome archive. Issue 3 (18th April 2022) - Fernández-Orth, Dietmar; Rueda, Manuel; Singh, Babita; Moldes, Mauricio; Jene, Aina; Ferri, Marta; Vasallo, Claudia; Fromont, Lauren A; Navarro, Arcadi; Rambla, Jordi
Abstract: Since its launch in 2008, the European Genome–Phenome Archive (EGA) has been leading the archiving and distribution of human identifiable genomic data. In this regard, one of the community concerns is the potential usability of the stored data, as of now, data submitters are not mandated to perform any quality control (QC) before uploading their data and associated metadata information. Here, we present a new File QC Portal developed at EGA, along with QC reports performed and created for 1 694 442 files [Fastq, sequence alignment map (SAM)/binary alignment map (BAM)/CRAM and variant call format (VCF)] submitted at EGA. QC reports allow anonymous EGA users to view summary-level information regarding the files within a specific dataset, such as quality of reads, alignment quality, number and type of variants and other features. Researchers benefit from being able to assess the quality of data prior to the data access decision and thereby, increasing the reusability of data (https://ega-archive.org/blog/data-upcycling-powered-by-ega/ ).